Attentive immobility in the face of inevitable distal threat—Startle potentiation and fear bradycardia as an index of emotion and attention. (24th March 2021) - Szeska, Christoph; Richter, Jan; Wendt, Julia; Weymar, Mathias; Hamm, Alfons O.
Abstract: During fear conditioning, a cue (CS) signals an inevitable distal threat (US) and evokes a conditioned response that can be described as attentive immobility (freezing). The organism remains motionless and monitors the source of danger while startle responses are potentiated, indicating a state of defensive hypervigilance. Although in animals vagally mediated fear bradycardia is also reliably observed under such circumstances, results are mixed in human fear conditioning. Using a single‐cue fear conditioning and extinction protocol, we tested cardiac reactivity and startle potentiation indexing low‐level defensive strategies in a fear‐conditioned ( n = 40; paired presentations of CS and US) compared with a non‐conditioned control group ( n = 40; unpaired presentations of CS and US). Additionally, we assessed shock expectancy ratings on a trial‐by‐trial basis indexing declarative knowledge of the previous contingencies. Half of each group underwent extinction under sham or active transcutaneous vagus nerve stimulation (tVNS), serving as additional proof of concept. We found stronger cardiac deceleration during CS presentation in the fear learning relative to the control group. This learned fear bradycardia was positively correlated with conditioned startle potentiation but not with declarative knowledge of CS‐US contingencies. TVNS abolished differences in heart rate changes between both groups and removed the significant correlation between late cardiac deceleration and startle potentiation in the fear learning group. Results suggest, fear‐conditioned cues evoke attentive immobility in humans, characterized by cardiac deceleration and startle potentiation. Such defensive response pattern is elicited by cues predicting inevitable distal threat and resembles conditioned fear responses observed in rodents. Abstract : Attentive immobility (freezing) describes a defensive response to threats, characterized by increased sensory intake, motor inhibition, cardiac deceleration, and a potentiation of the startle response. We found that cardiac deceleration and startle potentiation are highly correlated during fear conditioning and extinction, suggesting that anticipation of inevitable distal threats elicits a defensive motivational state in humans, which resembles the freezing response in animals.